2014
DOI: 10.1093/jrr/rrt146
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and toxicity of stereotactic body radiotherapy with helical tomotherapy for inoperable lung tumor: analysis of Grade 5 radiation pneumonitis

Abstract: To analyze outcomes and toxicities of stereotactic body radiotherapy with helical tomotherapy (HT-SBRT) for inoperable lung tumors, the medical records of 30 patients with 31 lung tumors treated with HT-SBRT were reviewed. The 3-year local control, cause-specific survival and overall survival rates (LC, CCS and OS, respectively) were analyzed using the Kaplan–Meier method. Toxicities were graded using Common Terminology Criteria for Adverse Events ver. 4. To investigate the factors associated with Grade 5 radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…14,15,22,23 Recently, the risk factors of RP after SBRT in patients with lung tumours have been investigated, 19,[22][23][24][25][26][27][28][29] and some studies reported about the clinical and dosimetric risk factors of RP. 21,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] Table 7 summarizes published reports of the clinical and dosimetric risk factors associated with Grade 2 or worse RP after SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,22,23 Recently, the risk factors of RP after SBRT in patients with lung tumours have been investigated, 19,[22][23][24][25][26][27][28][29] and some studies reported about the clinical and dosimetric risk factors of RP. 21,[29][30][31][32][33][34][35][36][37][38][39][40][41][42] Table 7 summarizes published reports of the clinical and dosimetric risk factors associated with Grade 2 or worse RP after SBRT.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the aforementioned disadvantages of HT compared with other stereotactic treatments in this setting, HTT is slow to be adopted in clinical practice, and few studies-often evaluating small series of patients with inhomogeneous characteristics and short FU-are available in the recent literature [9][10][11][12][13][14][15][16] (Table 4). Several points can be gleaned from this study, which to our knowledge is one among the largest series addressing the use of HTT in the treatment of lung lesions.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 While dosimetric findings have shown that such capabilities can potentially translate into the delivery of an increased tumour dose with doses to normal tissues decreased compared with other techniques, 7,8 only a limited number of patients were included in recent studies that have addressed the feasibility of hypofractionated or ablative radiotherapy (RT) regimens for lung tumours treated with HT. [9][10][11][12][13][14][15][16] Reasonable arguments might be advocated for its slow adoption in the clinical practice in this setting: during HT it is not only the tumour and the MLC that are moving but also the radiation source and couch, which can maximize the breathing interplay effect (i.e. difference between planned and delivered absorbed doses that arises from a mismatch between the tumour and the MLC because of motion).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the lung volume receiving lower dose may reduce the possibility of radiation pneumonitis. 23 …”
Section: Discussionmentioning
confidence: 99%